Secondary battery and preparation method thereof, energy storage battery pack and electric equipment

By forming a double-layer structure of carbon-coated camphor particles on the negative electrode, the problem of increased electrochemical impedance of the negative electrode is solved, the porosity and conductivity are improved, and the electrochemical performance and structural stability of the battery cell are enhanced.

CN121035119APending Publication Date: 2025-11-28ZHEJIANG JINKO ENERGY STORAGE CO LTD
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202511177091.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-05-26
Publication Date
2025-11-28

AI Technical Summary

Technical Problem

While existing technologies improve the energy density of battery cells, they also increase the electrochemical impedance of the negative electrode, leading to the risk of lithium plating and capacity decay. Furthermore, traditional methods affect porosity and electrode structure stability.

Method used

The negative electrode uses a double-layer structure formed by carbon-coated camphor particles. The first active layer has a first pore, and the second active layer has a second pore. The camphor particles are sublimated through drying to form a carbon-coated structure, which improves electronic conductivity and porosity.

Benefits of technology

It improves the porosity and electrochemical performance of the negative electrode, reduces the difficulty of electrolyte wetting, enhances the electronic conductivity and the bonding force between the electrode and the electrode, avoids the collapse of the coating structure, and improves the rate performance of the electrode.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN121035119A_ABST
    Figure CN121035119A_ABST
Patent Text Reader

Abstract

The invention relates to the field of energy storage, and provides a secondary battery and a preparation method thereof, an energy storage battery pack and electric equipment, and the preparation method comprises the following steps: forming a first active layer provided with a first hole and a second active layer provided with a second hole; the preparation method for forming the second active layer comprises the following steps: obtaining a camphor precursor based on second camphor particles and a pre-carbonization solution, and coating the surface of the camphor precursor with a carbonization material; carrying out heat treatment on the camphor precursor to obtain carbon-coated camphor particles; uniformly stirring the carbon-coated camphor particles, a second negative electrode material, a second conductive agent, a second adhesive and the second dispersion solution to obtain second coating slurry; the current collector with the first active layer is covered with second coating slurry, the second coating slurry can flow into part of the first holes, and a second active layer with carbon-coated second holes is formed after drying; and winding or laminating the positive plate, the negative plate and the diaphragm to obtain the secondary battery.
Need to check novelty before this filing date? Find Prior Art

Description

[0001] This application is a divisional application of the patent application with the application number 202510686854.8, the application date of May 26, 2025, and the invention name of "Secondary battery and preparation method thereof, energy storage battery pack and electric equipment". TECHNICAL FIELD

[0002] The present application relates to the field of energy storage, in particular to a secondary battery and a preparation method thereof, an energy storage battery pack and an electric equipment. BACKGROUND

[0003] With the rapid development of the energy storage market, energy storage battery cells are accelerating the update iteration. At present, the battery cell products are developing towards large capacity and high energy density. In addition to developing positive and negative electrode materials with higher specific capacity, in the battery cell design, the energy density of the battery cell is often improved by increasing the coating surface density of the pole piece and increasing the compaction density, but this will greatly increase the electrochemical impedance of the pole piece, especially for the negative pole piece. The increase of the electrochemical impedance of the pole piece will increase the risk of lithium precipitation in the charging process of the battery cell, resulting in the capacity attenuation of the battery cell.

[0004] At present, the methods or preparation processes for improving the electrochemical impedance and improving the energy density of the battery cell are relatively complex, and will affect the porosity of the negative pole piece and reduce the tortuosity of the pole piece, thereby causing new problems. SUMMARY

[0005] The embodiments of the present application provide a secondary battery and a preparation method thereof, an energy storage battery pack and an electric equipment, which at least have the advantages of improving the porosity of the negative pole piece, the electrochemical performance of the negative pole piece, and improving the rate performance of the pole piece.

[0006] According to some embodiments of the present application, the present application provides a preparation method of a secondary battery, comprising: forming a negative electrode sheet, the negative electrode sheet comprising: a negative electrode current collector, a first active layer, and a second active layer stacked in sequence, the first active layer having first pores, the second active layer having second pores, the second active layer having a second porosity greater than a first porosity of the first active layer; the preparation step of the second active layer comprising: preparing carbon-coated camphor particles; preparing a second coating slurry, the second coating slurry comprising the carbon-coated camphor particles; covering the second coating slurry on the negative electrode current collector with the first active layer, wherein the second coating slurry flows into at least part of the first pores, and performing a drying treatment to form the second active layer; wherein during the drying treatment, camphor particles in the carbon-coated camphor particles sublimate to form the second pores; providing a positive electrode sheet and a separator, stacking the negative electrode sheet, the separator, and the positive electrode sheet in sequence, obtaining a bare battery cell by winding or stacking, and placing the bare battery cell into a battery case, injecting an electrolyte into the battery case, and packaging to obtain a secondary battery.

[0007] In some embodiments, the second coating slurry further comprises: a second negative electrode material, a second conductive agent, and a second binder and a second dispersion solution; and the mass fraction ratio of the carbon-coated camphor particles, the second negative electrode material, the second conductive agent, the second binder, and the second dispersion solution is (0.4-0.6):(96-97.2):(0.4-0.6):(2.0-2.8):(160-200).

[0008] In some embodiments, the second binder comprises styrene-butadiene rubber, carboxymethyl cellulose, and polyacrylic acid, and the mass fraction ratio of the styrene-butadiene rubber, the carboxymethyl cellulose, and the polyacrylic acid is (0.8-1.2):(0.6-0.8):(0.6-0.8).

[0009] In some embodiments, in the process step of obtaining the second coating slurry, the carboxymethyl cellulose, the polyacrylic acid, and the styrene-butadiene rubber are sequentially added, and the stirring speed is controlled to show a trend of first increasing and then decreasing.

[0010] In some embodiments, the preparation step of the carbon-coated camphor particles comprises: dispersing second camphor particles in a pre-carbonization solution containing carbonization material, drying to obtain camphor precursors with the carbonization material coated on the surface, and performing a heat treatment on the camphor precursors to convert the camphor precursors into the carbon-coated camphor particles; the pre-carbonization solution comprises a sucrose aqueous solution, and the mass fraction of the sucrose aqueous solution in the pre-carbonization solution is 3-7 parts; and the mass fraction of the second camphor particles in the sucrose aqueous solution is 55wt%-70wt%.

[0011] In some embodiments, the heat treatment process includes: placing the camphor precursor in a heat treatment apparatus, introducing an inert gas, heating to 160°C to 200°C, carbonizing for 5 min to 15 min, and cooling to obtain the carbon-coated camphor particles; the thickness of the carbon shell in the carbon-coated camphor particles is 15 nm to 20 nm.

[0012] In some embodiments, the preparation step of forming the first active layer includes: stirring the first camphor particles, the first negative electrode material, the first conductive agent, and the first binder with a first dispersion solution to obtain a first coating slurry; and covering the negative electrode current collector with the first coating slurry at a density of 100 g / m³. 2 ~110g / m 2 After drying, the first active layer is obtained, wherein the first camphor particles sublimate after drying, and the positions occupied by the first camphor particles are transformed into the first pores.

[0013] In some embodiments, after forming the first active layer, the method further includes: providing a carbon source gas and a carrier gas, and forming a carbon nanotube layer on the surface of the first active layer using a plasma vapor deposition process at a temperature of 700°C to 900°C; the thickness of the carbon nanotube layer is 200 μm to 500 μm.

[0014] In some embodiments, the second particle size of the second camphor particle is smaller than the first particle size of the first camphor particle; the first particle size is 15μm to 20μm; and the second particle size is 5μm to 10μm.

[0015] In some embodiments, the mass ratio of the first camphor particles, the first negative electrode material, the first conductive agent, the first binder, and the first dispersion solution is (0.2-0.4):(96-97.2):(0.8-1.2):(2.0-2.8):(160-200).

[0016] In some embodiments, the first conductive agent comprises carbon nanotubes and conductive carbon black, and the mass ratio of the carbon nanotubes to the conductive carbon black is (0.4-0.6):(0.4-0.6).

[0017] According to some embodiments of this application, another aspect of this application provides a secondary battery prepared using the above-described secondary battery preparation method, comprising: a battery casing having a cavity inside the battery casing containing an electrolyte; a bare cell located within the cavity and immersed in the electrolyte; the bare cell comprising a positive electrode sheet, a separator, and a negative electrode sheet stacked together, wherein the negative electrode sheet comprises: a negative electrode current collector, a first active layer, and a second active layer, the first active layer being located on the surface of the current collector, the second active layer being located on the surface of the first active layer, the first active layer having a first pore, the second active layer having a second pore encased in a carbon shell, the second porosity of the second active layer being greater than the first porosity of the first active layer; the electrolyte is also located within the first pore and the second pore.

[0018] In some embodiments, the negative electrode further includes a carbon nanotube layer, which is located between the first active layer and the second active layer.

[0019] According to some embodiments of this application, another aspect of this application provides an energy storage battery pack, including: a secondary battery prepared by the method for preparing a secondary battery as described in any of the above embodiments, or a secondary battery as described in the above embodiments.

[0020] According to some embodiments of this application, another aspect of this application provides an electrical device, including: a secondary battery prepared by the method for preparing a secondary battery as described in any of the above embodiments, a secondary battery as described in the above embodiments, or an energy storage battery pack as described in the above embodiments.

[0021] The technical solution provided in this application has at least the following advantages:

[0022] The secondary battery fabrication method provided in this application embodiment involves setting a first active layer and a second active layer on the negative electrode current collector of the negative electrode sheet, wherein the second porosity of the second active layer is greater than the first porosity of the first active layer. This allows the electrolyte to penetrate the first active layer through the second pores of the second active layer, thereby reducing the difficulty of electrolyte wetting and improving electronic conductivity. Secondly, carbon-coated camphor particles are used as carriers for the second pores. After the second camphor particles sublimate, the carbon shell can support the void structure, effectively solving the problem of coating structure collapse caused by void creation, while simultaneously improving the electronic conductivity of the second active layer. Furthermore, the first active layer contains first pores, allowing the slurry to partially flow into the first pores during the formation of the second active layer, creating a pinning effect and improving the bonding force between the first and second active layers. Attached Figure Description

[0023] One or more embodiments are illustrated by way of example with reference to the accompanying drawings. These illustrations do not constitute a limitation on the embodiments. Unless otherwise stated, the drawings in the accompanying drawings do not constitute a limitation on scale. In order to more clearly illustrate the technical solutions in the embodiments of this application or in the conventional art, the drawings used in the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of this application. For those skilled in the art, other drawings can be obtained based on these drawings without creative effort.

[0024] Figure 1 A flowchart illustrating a method for preparing a secondary battery according to an embodiment of this application;

[0025] Figure 2 This is a schematic diagram of a structure of the negative electrode in a secondary battery provided in an embodiment of this application. Detailed Implementation

[0026] As can be seen from the background technology, the porosity, electrochemical performance, and rate performance of current negative electrode sheets need further improvement.

[0027] Analysis revealed that one of the reasons for the reduced porosity, electrochemical performance, and rate performance of the negative electrode lies in the fact that current methods to overcome the increased impedance caused by high areal density and high compaction typically involve adjusting the ratio of positive and negative electrode formulations. For example, increasing the proportion of conductive particles increases the electronic conductivity of the electrode. To improve ionic conductivity, a reasonable particle size ratio is usually used to increase electrode porosity and reduce electrode tortuosity. However, these measures have limited effectiveness in addressing the increased electrode impedance. A reasonable active material particle size ratio does not significantly improve the ionic conductivity of the electrode, and the porosity distribution remains unreasonable. Simply increasing the proportion of conductive particles can reduce the electronic resistance of the electrode to a certain extent, but since ionic impedance is a weak point of the electrode, its effect on improving the overall electrochemical impedance is negligible. Therefore, simultaneously improving both the electronic and ionic conductivity of the negative electrode is crucial to effectively improve its electrochemical performance and rate performance. In addition, pore-forming agents are also used to increase porosity. Although these methods can increase the ionic conductivity of the electrode, they can also easily cause the electrode structure to collapse.

[0028] This application provides a secondary battery and its preparation method, energy storage battery pack and electrical equipment. By using camphor particles to sublimate and form pores, and by encapsulating the camphor particles with carbon to ensure the stability of the pores and prevent the pores from collapsing, the conductivity is improved by the first active layer, the second active layer and the carbon shell, thereby improving the electrochemical performance and rate performance of the negative electrode.

[0029] In the description of the embodiments of this application, technical terms such as "first" and "second" are used only to distinguish different objects and should not be construed as indicating or implying relative importance or implicitly specifying the number, specific order, or primary and secondary relationship of the indicated technical features. In the description of the embodiments of this application, "multiple" means two or more, unless otherwise explicitly defined.

[0030] In this document, the term "embodiment" means that a particular feature, structure, or characteristic described in connection with an embodiment may be included in at least one embodiment of this application. The appearance of this phrase in various places throughout the specification does not necessarily refer to the same embodiment, nor is it a separate or alternative embodiment mutually exclusive with other embodiments. It will be explicitly and implicitly understood by those skilled in the art that the embodiments described herein can be combined with other embodiments.

[0031] In the description of the embodiments in this application, the term "and / or" is merely a description of the relationship between related objects, indicating that three relationships can exist. For example, A and / or B can represent three cases: A exists, A and B exist simultaneously, and B exists. In addition, the character " / " in this document generally indicates that the related objects before and after it have an "or" relationship.

[0032] In the description of the embodiments of this application, the term "multiple" refers to two or more (including two), similarly, "multiple sets" refers to two or more (including two sets), and "multiple pieces" refers to two or more (including two pieces).

[0033] In the description of the embodiments of this application, the technical terms "center," "longitudinal," "lateral," "length," "width," "thickness," "upper," "lower," "front," "rear," "left," "right," "vertical," "horizontal," "top," "bottom," "inner," "outer," "clockwise," "counterclockwise," "axial," "radial," and "circumferential" indicate the orientation or positional relationship based on the orientation or positional relationship shown in the accompanying drawings. They are only for the convenience of describing the embodiments of this application and simplifying the description, and are not intended to indicate or imply that the device or element referred to must have a specific orientation, or be constructed and operated in a specific orientation. Therefore, they should not be construed as limitations on the embodiments of this application.

[0034] In the description of the embodiments of this application, unless otherwise expressly specified and limited, the technical terms such as "installation," "connection," "joining," and "fixing" should be interpreted broadly. For example, they can refer to a fixed connection, a detachable connection, or an integral part; they can refer to a mechanical connection or an electrical connection; they can refer to a direct connection or an indirect connection through an intermediate medium; they can refer to the internal communication of two components or the interaction between two components. For those skilled in the art, the specific meaning of the above terms in the embodiments of this application can be understood according to the specific circumstances.

[0035] In the accompanying drawings corresponding to the embodiments of this application, the thickness and area of ​​the layers are enlarged for better understanding and ease of description. When describing a component (such as a layer, film, region, or substrate) on or on the surface of another component, the component may be "directly" located on the surface of the other component, or there may be a third component between the two components. Conversely, when describing a component on the surface of another component, or when another component is formed or disposed on the surface of a component, it indicates that there is no third component between the two components. Furthermore, when describing a component as being "generally" formed on another component, it means that the component is not formed on the entire surface (or front surface) of the other component, nor is it formed on a portion of the edge of the entire surface.

[0036] In the description of the embodiments of this application, when a component "includes" another component, other components are not excluded unless otherwise stated, and other components may be further included. Furthermore, when a component such as a layer, film, region, or plate is referred to as being "on / located" on another component, it can be "directly on" the other component (i.e., located on the surface of the other component with no other components between them), or it can have another component present in between. Moreover, when a component such as a layer, film, region, or plate is "directly located" on another component, or when a component such as a layer, film, region, or plate is located on the surface of another component, it indicates that no other components are located in between.

[0037] The terminology used in the description of the various embodiments herein is for the purpose of describing particular embodiments only and is not intended to be limiting. As used in the description of the various embodiments and the appended claims, the term "part" is also intended to include the plural form unless the context clearly indicates otherwise. Components include layers, films, regions, or plates, etc.

[0038] The embodiments of this application will now be described in detail with reference to the accompanying drawings. However, those skilled in the art will understand that many technical details have been provided in the embodiments of this application to facilitate a better understanding of the application. However, the technical solutions claimed in this application can be implemented even without these technical details and various variations and modifications based on the following embodiments.

[0039] Figure 1 A flowchart illustrating a method for preparing a secondary battery according to an embodiment of this application; Figure 2 This is a schematic diagram of a structure of the negative electrode in a secondary battery provided in an embodiment of this application.

[0040] According to some embodiments of this application, one embodiment of this application provides a method for preparing a secondary battery, referring to... Figure 1The preparation method includes: forming a negative electrode sheet, the negative electrode sheet comprising: a negative electrode current collector, a first active layer, and a second active layer stacked sequentially, the first active layer having a first pore, the second active layer having a second pore, the second porosity of the second active layer being greater than the first porosity of the first active layer; the preparation step of forming the second active layer includes: preparing carbon-coated camphor particles; preparing a second coating slurry, the second coating slurry comprising carbon-coated camphor particles; covering the negative electrode current collector having the first active layer with the second coating slurry, wherein the second coating slurry flows into at least part of the first pores, and is dried to form the second active layer; wherein, during the drying process, the camphor particles in the carbon-coated camphor particles sublimate to form the second pores; providing a positive electrode sheet and a separator, stacking the negative electrode sheet, separator, and positive electrode sheet sequentially, obtaining a bare cell by winding or stacking, placing the bare cell into a battery case, injecting electrolyte into the battery case, and then encapsulating it to obtain a secondary battery.

[0041] A negative electrode sheet is formed, comprising: a negative electrode current collector, a first active layer, and a second active layer. The first active layer is located on the surface of the negative electrode current collector, and the second active layer is located on the surface of the first active layer away from the first active layer. The first active layer has a first pore, and the second active layer has a second pore. The second porosity of the second active layer is greater than the first porosity of the first active layer. The preparation step of forming the second active layer includes: dispersing second camphor particles in a pre-carbonization solution containing carbonization material, drying to obtain a camphor precursor, and coating the surface of the camphor precursor with carbonization material; and further processing the camphor precursor... Heat treatment is performed to convert the camphor precursor into carbon-coated camphor particles; the carbon-coated camphor particles, the second negative electrode material, the second conductive agent, and the second binder are stirred evenly with the second dispersion solution to obtain a second coating slurry; the second coating slurry is applied to the negative electrode current collector having the first active layer, wherein the second coating slurry flows into at least part of the first pores, and after drying, a second active layer is formed; wherein the camphor particles in the carbon-coated camphor particles sublimate after drying, the carbon shell of the carbon-coated camphor particles is retained, and the positions occupied by the camphor particles in the carbon-coated camphor particles are transformed into second pores with carbon coating.

[0042] The secondary battery fabrication method provided in this application embodiment involves setting a first active layer and a second active layer on the negative electrode current collector of the negative electrode sheet, wherein the second porosity of the second active layer is greater than the first porosity of the first active layer. This allows the electrolyte to penetrate the first active layer through the second pores of the second active layer, thereby reducing the difficulty of electrolyte wetting and improving electronic conductivity. Secondly, carbon-coated camphor particles are used as carriers for the second pores. After the second camphor particles sublimate, the carbon shell can support the void structure, effectively solving the problem of coating structure collapse caused by void creation, while simultaneously improving the electronic conductivity of the second active layer. Furthermore, the first active layer contains first pores, allowing the slurry to partially flow into the first pores during the formation of the second active layer, creating a pinning effect and improving the bonding force between the first and second active layers.

[0043] The preparation method described above will be explained in detail below.

[0044] According to their shape, the prepared secondary batteries can be classified into square cells, round cells, or pouch cells. According to their capacity, secondary batteries can be classified into models such as 50Ah, 100Ah, 150Ah, 200Ah, 280Ah, 306Ah, 314Ah, 500+Ah, 800+Ah, and 1000+Ah. According to the chemical composition and working principle of the bare battery cells, secondary batteries can be lithium-ion batteries, lead-acid batteries, sodium-ion batteries, or nickel-metal hydride batteries. This application uses a lithium-ion battery preparation method as an example. Those skilled in the art can replace the lithium ions in the positive electrode, negative electrode, and electrolyte with corresponding metal ions according to actual needs. For example, in sodium-ion batteries, the lithium transition metal oxide of the positive electrode active material can be replaced with any of the following: a layered metal oxide (e.g., NaFeO2), a polyanionic compound (NaFePO4), or a Prussian blue compound system (e.g., NaMnFe(CN)6-zH2O), and the electrolyte can be replaced with any of the following: an organic liquid electrolyte, a solid composite electrolyte, or a solid electrolyte.

[0045] refer to Figure 2 The negative electrode current collector 100 can be copper foil. Copper foil has low conductivity, which allows for high electron transport capability. Furthermore, copper foil has weak lithium intercalation capability, capturing fewer lithium ions and thus effectively reducing lithium ion loss. In other embodiments, the negative electrode current collector can also be a foamed copper current collector, a copper mesh current collector, or a three-dimensional nano-copper array current collector.

[0046] In some embodiments, the negative electrode current collector 100 can be a composite current collector, including a polymer material layer and a metal coating. The metal coating is located on the upper and lower sides of the polymer material layer. The polymer material layer is PET (polyterephthalate), PP (polypropylene), PI (polyimide), etc., and the metal coating is a copper layer.

[0047] In some embodiments, the negative electrode current collector 100 can also be a carbon-based current collector, i.e., a conductive carbon layer is formed on the copper foil. The conductive carbon layer can serve as a protective layer to effectively protect the current collector, preventing corrosion of the metal current collector and thus improving its lifespan. Secondly, the conductive carbon layer itself has low resistivity, thus minimizing electrical losses. The material of the conductive carbon layer can be flake graphite, spherical graphite, carbon nanotubes, graphene, etc.

[0048] It should be noted that the carbon-based current collector can be characterized by both the upper and lower surfaces of the copper foil being covered with a conductive carbon layer, or by a portion of the copper foil surface being covered with a conductive carbon layer. Specifically, the portion of the copper foil surface covered with a conductive carbon layer may have a conductive carbon layer on the copper foil corresponding to the first active layer (and a portion of the tab area not covered by the first active layer); or the tab area may have a conductive carbon layer; or the first active layer and a portion of the tab area may have a conductive carbon layer, etc.

[0049] In some embodiments, the active material particles in the first active layer 110 and the second active layer 130 are carriers for the oxidation reaction of the battery cell, such as the negative electrode material in the first active layer and the negative electrode material in the second active layer.

[0050] In some embodiments, the negative electrode active material can be divided into two main categories: carbon materials and non-carbon materials. Carbon materials include graphite materials (natural graphite, artificial graphite, and mesophase carbon spheres) and other carbon materials (hard carbon, soft carbon, and graphene). Non-carbon materials can be further subdivided into titanium-based materials, silicon-based materials, tin-based materials, nitrides, and lithium metal, etc.

[0051] In some embodiments, a first active layer 110 and a second active layer 130 are provided on the negative electrode current collector 100. The arrangement of the two active material layers serves two purposes: first, the first active layer 110 is closer to the negative electrode current collector 100, so that the lower surface of the negative electrode current collector 100 connected to the active coating has better stability and conductivity, thereby improving the electrochemical performance and cycle performance of the negative electrode; second, the second active layer 130, which is far away from the negative electrode current collector 100, is in contact with the separator, and lithium plating is prone to occur on the surface of its corresponding negative electrode side. Therefore, the second active layer 130 in contact with the separator can focus on stability and conductivity, which is conducive to the smooth insertion and extraction of lithium ions inside the positive and negative electrode materials.

[0052] Thus, the second active layer 130 has a second pore 131, and the first active layer 110 has a first pore 111. The second porosity of the second active layer 130 is greater than the first porosity of the first active layer 110. The second pore 131 can increase the porosity of the negative electrode, which is beneficial for electrolyte storage and effectively improves the electrolyte retention capacity of the negative electrode. During charging and discharging, it reduces the lithium ion transport distance, resulting in gaps between the active material particles of the negative electrode, providing buffer space for the cyclic expansion inside the active material particles, and further improving the charging capacity of the negative electrode.

[0053] In some embodiments, the preparation step of forming the first active layer 110 includes: stirring the first camphor particles, the first negative electrode material, the first conductive agent and the first binder with the first dispersion solution to obtain the first coating slurry.

[0054] In some embodiments, the first camphor particle is named 1,7,7-trimethylbicyclo[2.2.1]heptane-2-one, with the chemical formula C 10 H 16 O. The average particle size of the first camphor particles is 15μm to 20μm. Particle size refers to the diameter of the particle, and the average particle size refers to the average diameter of most particles or the average length of irregular particles.

[0055] In some embodiments, the mass ratio of the first camphor particles, the first negative electrode material, the first conductive agent, the first binder, and the first dispersion solution in the first coating slurry is (0.2–0.4):(96–97.2):(0.8–1.2):(2.0–2.8):(160–200). Thus, increasing the proportion of the first conductive agent to 0.8–1.2, compared to the conventional conductive agent proportion of 0.4–0.6 (e.g., the mass ratio of the second conductive agent), can increase the proportion of conductive particles in the negative electrode active material, thereby improving the electronic conductivity of the first active layer 110, and consequently improving the electrochemical performance and cycle performance of the negative electrode sheet.

[0056] In some embodiments, the first negative electrode material may include graphite. The graphite may be secondary-particle graphite, which has a smaller volume, making it more suitable for ion diffusion. Secondary-particle graphite can provide lower impedance properties, thus exhibiting higher conductivity. Here, secondary particles refer to the particle size of the aggregated particles, while primary particles refer to the particle size of an individual fine grain.

[0057] In some embodiments, the first conductive agent includes carbon nanotubes (CNTs) and conductive carbon black (SP), and the mass ratio of carbon nanotubes to conductive carbon black is (0.4-0.6):(0.4-0.6).

[0058] In some embodiments, the first adhesive includes styrene-butadiene rubber (SBR), carboxymethyl cellulose (CMC), and polyacrylic acid (PAA), with a mass ratio of SBR, CMC, and PAA of (0.8–1.2):(0.6–0.8):(0.6–0.8). The use of an aqueous solution of SBR as the adhesive reduces electrode delamination and decarburization during coating, cutting, slitting, and winding processes, optimizes electrode processing performance, and results in electrodes with good flexibility. Carboxymethyl cellulose primarily acts as a dispersant and thickener, thereby reducing the amount of adhesive required. Polyacrylic acid is a water-soluble polymer polymerized from acrylic acid monomers. The presence of numerous carboxylic acid groups on polyacrylic acid allows for strong interactions with active materials, resulting in good adhesion and improved cycle stability during battery cell cycling.

[0059] In some embodiments, the first dispersion solution may be deionized water.

[0060] In summary, the process for forming the first coating slurry provided in this application embodiment can be as follows: the mass ratio of each substance is: graphite (first negative electrode material): 96 parts to 97.2 parts, PAA (first binder): 0.6 parts to 0.8 parts, SBR (first binder): 0.8 parts to 1.2 parts, CMC (first binder): 0.6 parts to 0.8 parts, SP (first conductive agent): 0.4 parts to 0.6 parts, CNT (first conductive agent): 0.4 parts to 0.6 parts, first camphor particles: 0.2 parts to 0.4 parts, and deionized water: 160 parts to 200 parts. The above amounts of graphite powder, SP, CMC, and first camphor particles are added to a mixing tank and dry-mixed for 30 minutes at a stirring speed of 15 rpm and a dispersion speed of 500 rpm. Next, add a small portion (e.g., 80 parts by weight) of deionized water and knead and stir for 60 minutes at a stirring speed of 20 rpm and a dispersion speed of 300 rpm. Then add the remaining deionized water (e.g., 105 parts by weight) and disperse at high speed at a stirring speed of 22 rpm and a dispersion speed of 1000 rpm. Then add CNT and PAA and disperse for 30 minutes at a stirring speed of 22 rpm and a dispersion speed of 600 rpm. Finally, add SBR and continue stirring for 30 minutes at a stirring speed of 22 rpm and a dispersion speed of 500 rpm to obtain the first coating slurry.

[0061] Continue to refer to Figure 1 The preparation steps for forming the first active layer 110 include: coating the negative electrode current collector 100 with a first coating slurry at a density of 100 g / m³. 2 ~110g / m 2After drying, the first active layer 110 is obtained, the first camphor particles are sublimated, and the positions occupied by the first camphor particles are transformed into the first pores 111.

[0062] In some embodiments, after the first coating slurry is applied to the negative electrode current collector, it is baked at 80°C for 12 hours. During the baking process, the first camphor particles will sublimate and detach from the coating, leaving a hole in the original position, namely the first hole 111, which facilitates the flow of the subsequent second coating slurry and forms the second active layer 130. Thus, the second active layer 130 is not only located on the surface of the first active layer 110, but also inside the first active layer 110, thereby playing a pinning effect and effectively improving the bonding force between the first active layer 110 and the second active layer 130.

[0063] In other embodiments, an electrolytic graphite pore-forming process can be employed. This involves mixing the raw materials (excluding the first camphor particles), coating and drying them to obtain a first active layer. The first active layer is then placed in an electrolytic cell, and the negative current collector is connected to a power source. When current flows through the electrolytic cell, the ions in the electrolyte are electrolyzed, resulting in a chemical reaction. This chemical reaction leads to etching of the graphite surface, forming pores, i.e., the first pores.

[0064] In some embodiments, reference Figure 2 After forming the first active layer 110, the process further includes providing a carbon source gas and a carrier gas, and forming a carbon nanotube layer 120 on the surface of the first active layer 110 using a plasma vapor deposition process at a temperature of 700℃ to 900℃. The carbon nanotube layer 120 effectively reduces the impedance caused by the coating interface and improves the lateral electronic conductivity of the coating.

[0065] In some embodiments, the thickness of the carbon nanotube layer 120 is 200 μm to 500 μm. The thickness of the carbon nanotube layer 120 can be 200 μm, 230 μm, 250 μm, 282 μm, 303 μm, 348 μm, 369 μm, 391 μm, 403 μm, 431 μm, 466 μm, 482 μm, or 500 μm. The thickness of the carbon nanotube layer 120 allows the subsequently formed second coating slurry to flow into the first pore 111 through the pores of the carbon nanotube layer 120, and also allows the electrolyte to flow into the first active layer 110 through these pores. Furthermore, the thickness of the carbon nanotube layer 120 can improve conductivity, thereby reducing the impedance between the first active layer 110 and the second active layer 130.

[0066] In some embodiments, the carbon source gas can be methane or ethanol. The carrier gas can be an inert gas such as argon.

[0067] Continue to refer to Figure 1The steps for forming the second active layer 130 can be divided into: forming a camphor precursor, coating the surface of the camphor precursor with a carbonized material; forming carbon-coated camphor particles; forming a second coating slurry; and forming the second active layer 130.

[0068] The process steps for forming the camphor precursor include: dissolving camphor particles in ethanol to form a saturated solution, obtaining micron-sized second camphor particles by spray drying, dispersing the second camphor particles in a pre-carbonization solution, stirring to evaporate the solvent, so that the carbonization material uniformly coats the second camphor particles, and drying to obtain the camphor precursor, with the surface of the camphor precursor coated with carbonization material.

[0069] In some embodiments, the precarbonation solution comprises a sucrose aqueous solution, wherein the sucrose aqueous solution comprises 3 to 7 parts by mass; and the camphor particles comprise 55 wt% to 70 wt% of the sucrose aqueous solution by mass.

[0070] The second camphor particles can be made of the same material as the first camphor particles, but the average particle size of the first camphor particles is smaller than that of the second camphor particles. The average particle size of the first camphor particles is 15μm to 20μm; the average particle size of the second camphor particles is 5μm to 10μm.

[0071] The average particle size of the second camphor particles can be 5μm, 6μm, 7μm, 8μm, 9μm or 10μm.

[0072] In some embodiments, the heat treatment process includes: placing the camphor precursor in a heat treatment apparatus, introducing an inert gas, heating to 160°C–200°C, and carbonizing for 5–15 minutes, followed by cooling to obtain carbon-coated camphor particles. The carbonization process controls the carbonization temperature and time to prevent excessive sublimation of the second camphor particles, and cooling yields carbon-coated camphor particles. The carbon shell retained in the carbon-coated camphor particles effectively supports the structure, preventing electrode structure collapse, and simultaneously improving the electronic conductivity of the second active layer 130.

[0073] In some embodiments, the thickness of the carbon shell 132 in the carbon-coated camphor particles is 15nm to 20nm, for example, the thickness of the carbon shell 132 can be 15nm, 16nm, 17nm, 18nm, 19nm or 20nm.

[0074] In some embodiments, the mass ratio of carbon-coated camphor particles, second negative electrode material, second conductive agent, second binder, and second dispersion solution is (0.4-0.6):(96-97.2):(0.4-0.6):(2.0-2.8):(160-200).

[0075] In some embodiments, the second adhesive comprises styrene-butadiene rubber, carboxymethyl cellulose, and polyacrylic acid, wherein the mass ratio of styrene-butadiene rubber, carboxymethyl cellulose, and polyacrylic acid is (0.8–1.2):(0.6–0.8):(0.6–0.8).

[0076] It should be noted that the second conductive agent in the second coating slurry is SP. The second negative electrode material is primary particulate graphite. The other components, the second binder, and the second dispersion are the same as the first binder and the first dispersion in the first coating slurry.

[0077] In some embodiments, in the process of obtaining the second coating slurry, carboxymethyl cellulose, polyacrylic acid and styrene-butadiene rubber are added sequentially, while the stirring speed is controlled to first increase and then decrease.

[0078] Specifically, the mass ratios of the substances are as follows: graphite (primary granules): 96-97.2 parts, PAA: 0.6-0.8 parts, SBR: 0.8-1.2 parts, CMC: 0.6-0.8 parts, SP: 0.4-0.6 parts, carbon-coated camphor granules: 0.4-0.6 parts, and deionized water: 160-200 parts. The above amounts of graphite powder, SP, CMC, and carbon-coated camphor granules are added to a mixing tank and dry-mixed for 30 minutes at a stirring speed of 15 rpm and a dispersion speed of 500 rpm. Then, a small amount (80 parts by mass) of deionized water is added and kneaded for 60 minutes at a stirring speed of 20 rpm and a dispersion speed of 300 rpm. Then add the remaining deionized water (105 parts by mass) and disperse at high speed with a stirring speed of 22 rpm and a dispersion speed of 1000 rpm. Then add PAA and disperse for 30 minutes with a stirring speed of 22 rpm and a dispersion speed of 600 rpm. Finally, add SBR and continue stirring for 30 minutes with a stirring speed of 22 rpm and a dispersion speed of 500 rpm to obtain the second coating slurry.

[0079] The process steps for forming the second active layer 130 include: applying a second coating slurry onto the first active layer 110 after the aforementioned surface treatment, with a coating surface density of 100 g / m². 2 ~110g / m 2 During the coating process, some of the coating slurry flows into the first pore 111. The double-layer negative electrode obtained by the above coating is then rolled to achieve a compaction density of 1.5 g / cm³. 3 ~1.6g / cm 3During the process, the rolled electrode is baked at 60°C for 24 hours. During the baking process, the camphor particles in the carbon-coated camphor particles will sublimate and detach from the coating, thereby effectively increasing the porosity of the second active layer 130 and improving its ionic conductivity. At the same time, the retained carbon coating layer can improve the electronic conductivity of the layer. Combined with the excellent electronic conductivity of the first active layer 110 and the carbon nanotube layer 120 coating, it also makes up for the problem of large ionic impedance when the thick negative electrode is close to the current collector and large electronic impedance when it is far away from the current collector. The negative electrode exhibits excellent rate performance.

[0080] It should be noted that the surface density of the first coating slurry and the second coating slurry can be determined according to the actual situation. The second coating slurry will partially fill the first pores 111, but will not completely fill them, so that some of the first pores 111 can still be used to fill the electrolyte, while the first pores filled with the second coating slurry are part of the second active layer.

[0081] In summary, for the first active layer 110, measures such as using secondary particle type graphite for the first active layer 110 near the negative electrode current collector, increasing the proportion of conductive particles, and introducing a carbon nanotube layer 120 to increase conductivity are taken to maximize the improvement of the electronic conductivity of this layer. This ensures the electronic conductivity of the second active layer 130 far from the negative electrode current collector. At the same time, in order to ensure the connection in the coating and to improve the ionic conductivity of the first active layer 110, camphor particles are used to create pores in the first active layer 110. Meanwhile, a carbon nanotube layer 120 is deposited on the surface of the first active layer 110 by vapor deposition, which effectively reduces the impedance caused by the coating interface and improves the lateral electronic conductivity of the coating.

[0082] For the second active layer 130, a template method is used to improve its porosity and thus its ionic conductivity. This template method involves adding thermally sublimable solid particles such as 1,7,7-trimethyldicycloheptan-2-one (camphor), whose surface is coated with carbon, to the coating slurry. During subsequent electrode baking, these particles sublimate, effectively increasing the porosity of this coating layer. Since the second active layer 130 is a surface coating, the application of the template method ensures that the template particles volatilize upon heating, without affecting the electrical performance of the subsequent electrode. The increased porosity of the second active layer 130 maximizes the ionic conductivity of the first active layer 110. Furthermore, when the camphor sublimates, the remaining carbon shell effectively supports the structure, preventing electrode collapse and simultaneously improving the electronic conductivity of the second active layer 130. The design of the first active layer 110 and the second active layer 130 effectively ensures the rate performance of the high-coating layer.

[0083] After forming the negative electrode sheet, the process also includes: die-cutting a portion of the negative electrode current collector according to preset parameters so that the ends of the negative electrode current collector form negative electrode tabs; cutting the negative electrode current collector to form multiple identical negative electrode sheets.

[0084] The positive electrode sheet includes a positive current collector and a positive active material layer, wherein the positive current collector can be aluminum foil.

[0085] The separator can be located between the positive and negative electrodes to prevent short circuits caused by physical contact between the positive and negative electrodes. At the same time, it allows ions to conduct through the electrolyte while hindering electron transport, so that ions and electrons can form a circuit during the charging and discharging process of the battery.

[0086] The diaphragm can be any of the following: microporous membrane, modified microporous membrane, nonwoven membrane, and composite membrane. The diaphragm can be coated with polyvinylidene fluoride (PVDF) to give it excellent adhesion and flexibility.

[0087] refer to Figure 1 The positive electrode, negative electrode, and separator are wound or stacked.

[0088] In some embodiments, the winding process involves using a winding machine to form a single core from the separator, positive electrode sheet, and negative electrode sheet. The sequence is to wrap the positive electrode sheet with the negative electrode sheet, and then separate the positive and negative electrode sheets using the separator. The stacking process involves stacking the separator, positive electrode sheet, and negative electrode sheet in sequence, and then forming a single battery cell through rolling and cutting.

[0089] The preparation method also includes: welding tabs to the adapter plate, connecting the other end of the adapter plate to the terminal post; and snapping the top cover into the battery casing. The adapter plate is located within the cavity, and the terminal post passes through the top cover.

[0090] The adapter includes at least a first adapter and a second adapter, and the terminal includes a positive terminal and a negative terminal. The first adapter is electrically connected to the positive electrode tab and the positive terminal of the positive electrode, and the second adapter is electrically connected to the negative electrode tab and the negative terminal of the negative electrode.

[0091] The secondary battery preparation method provided in this application embodiment involves setting a first active layer 110 and a second active layer 130 on the negative electrode current collector of the negative electrode sheet. The second porosity of the second active layer 130 is greater than the first porosity of the first active layer 110. This allows the electrolyte to penetrate into the first active layer 110 through the second pores 131 of the second active layer, thereby reducing the difficulty of electrolyte wetting and improving electronic conductivity. Secondly, carbon-coated camphor particles are used as the carrier for the second pores 131. After the second camphor particles sublimate, the carbon shell 132 can support the void structure, effectively solving the problem of coating structure collapse caused by void creation, and simultaneously improving the electronic conductivity of the second active layer 130. Furthermore, the first active layer 110 has first pores 111. When the second active layer 130 is formed, the slurry can partially flow into the first pores 111 to exert a pinning effect, improving the bonding force between the first active layer 110 and the second active layer 130.

[0092] Accordingly, according to some embodiments of this application, another aspect of the embodiments of this application also provides a secondary battery, which can be prepared by the preparation method provided in the above embodiments, and the same or corresponding technical features as the above embodiments will not be described in detail here.

[0093] According to some embodiments of this application, another aspect of this application provides a secondary battery, including: a battery casing having a cavity inside the battery casing containing an electrolyte; a bare battery cell located inside the cavity and immersed in the electrolyte; the bare battery cell includes a positive electrode sheet, a separator, and a negative electrode sheet stacked together, wherein the negative electrode sheet includes: a negative electrode current collector 100, a first active layer 110, and a second active layer 130, the first active layer 110 being located on the surface of the current collector, the second active layer 130 being located on the surface of the first active layer 110, the first active layer 110 having a first pore 111, the second active layer 130 having a second pore 131 covered by a carbon shell 132, the second porosity of the second active layer 130 being greater than the first porosity of the first active layer 110; the electrolyte is also located inside the first pore 111 and the second pore 131.

[0094] In some embodiments, the negative electrode further includes a carbon nanotube layer 120, which is located between the first active layer 110 and the second active layer 130.

[0095] According to some embodiments of this application, another aspect of this application provides an energy storage battery pack, including: a secondary battery prepared by the secondary battery preparation method of any of the above embodiments or a secondary battery as described in the above embodiments.

[0096] According to some embodiments of this application, another aspect of this application provides an electrical device, including: a secondary battery prepared by the method for preparing a secondary battery as described in any of the above embodiments, a secondary battery as described in the above embodiments, or an energy storage battery pack as described in the above embodiments.

[0097] The beneficial effects of the embodiments of this application will be further illustrated below with reference to examples and comparative examples.

[0098] Example 1:

[0099] (1) Preparation of the first coating slurry: The mass fractions of each substance are as follows: graphite (raw material is secondary particles): 96.4 parts, PAA: 0.6 parts, SBR: 1.2 parts, CMC: 0.6 parts, SP: 0.4 parts, CNT: 0.4 parts, first camphor particles: 0.4 parts, deionized water: 185 parts. The above amounts of graphite powder, SP, CMC and first camphor particles are added to a mixing tank and dry-mixed for 30 minutes at a stirring speed of 15 rpm and a dispersion speed of 500 rpm. Then, 80 parts of deionized water are added and kneaded for 60 minutes at a stirring speed of 20 rpm and a dispersion speed of 300 rpm. Then add the remaining deionized water (105 parts) and disperse at high speed. The stirring speed is 22 rpm and the dispersion speed is 1000 rpm. Then add CNT and PAA and disperse for 30 minutes. The stirring speed is 22 rpm and the dispersion speed is 600 rpm. Finally, add SBR and continue stirring for 30 minutes. The stirring speed is 22 rpm and the dispersion speed is 500 rpm to obtain the first coating slurry.

[0100] (2) Preparation of the first active layer and the carbon nanotube layer:

[0101] The first coating slurry was applied to the copper foil, with a coating surface density of 105 g / m². 2 The coated electrode is baked at 80℃ for 12 hours. During baking, the first camphor particles sublimate and detach from the coating, leaving the first pores and forming the first active layer. This facilitates the flow of the subsequent coating slurry and provides a pinning effect. Carbon nanotubes are then grown on the baked electrode surface. A carbon source gas (methane or ethanol) and a carrier gas (argon) are introduced into the reactor in a specific ratio. Under high temperature (700℃) and high pressure, the carbon source gas decomposes. The decomposed carbon source gas is then cooled in stages and used to bombard the first active layer. After a period of gas bombardment, a carbon nanotube layer is formed on its surface. The thickness of the carbon nanotube layer is 300 μm.

[0102] (3) Preparation of carbon-coated camphor particles:

[0103] A certain amount of camphor was dissolved in ethanol to form a saturated solution. Micron-sized second camphor particles were obtained by spray drying. These second camphor particles were then dispersed in a sucrose aqueous solution (7 parts by mass, with the second camphor particles comprising 55 wt% of the solution). The solvent was evaporated by stirring, allowing the sugar to uniformly coat the second camphor particles. The mixture was then dried to obtain sugar-camphor composite particles, i.e., the camphor precursor. The coated camphor precursor was placed in a tube furnace and rapidly heated to 180°C using an inert gas atmosphere. The temperature was maintained for 15 minutes to carbonize the precursor. Cooling yielded carbon-coated camphor particles with a carbon shell thickness of 20 nm.

[0104] (4) Preparation of the second coating slurry:

[0105] The mass fractions of each substance are as follows: graphite (raw material is primary granules): 97 parts, PAA: 0.6 parts, SBR: 0.8 parts, CMC: 0.6 parts, SP: 0.4 parts, carbon-coated camphor granules: 0.6 parts, and deionized water: 185 parts. The above amounts of graphite powder, SP, CMC, and carbon-coated camphor granules are added to a mixing tank and dry-mixed for 30 minutes at a stirring speed of 15 rpm and a dispersion speed of 500 rpm. Then, 80 parts of deionized water are added and kneaded for 60 minutes at a stirring speed of 20 rpm and a dispersion speed of 300 rpm. Then add the remaining deionized water (105 parts) and disperse at high speed with a stirring speed of 22 rpm and a dispersion speed of 1000 rpm. Then add PAA and disperse for 30 minutes with a stirring speed of 22 rpm and a dispersion speed of 600 rpm. Finally, add SBR and continue stirring for 30 minutes with a stirring speed of 22 rpm and a dispersion speed of 500 rpm to obtain the second coating slurry.

[0106] (5) Preparation of the second active layer:

[0107] The second coating slurry is applied to the first active layer after the aforementioned surface treatment, with a coating surface density of 105 g / m². 2 During the coating process, some of the second coating slurry flows into the first pores. The resulting double-layer negative electrode sheet is then rolled to achieve a compaction density of 1.5 g / cm³. 3 ~1.6g / cm 3 Between these processes, the rolled electrode sheets are baked at 60°C for 24 hours. During the baking process, the camphor in the carbon-coated camphor will sublimate and detach from the coating, thereby forming a second pore and a second active layer.

[0108] Example 2:

[0109] The difference from Example 1 is that the mass fraction of the first camphor particles in the first active layer is 0.2 parts.

[0110] Example 3:

[0111] The difference from Example 1 is that the carbon-coated camphor particles in the second active layer have a mass fraction of 0.4 parts.

[0112] Example 4:

[0113] The difference from Example 1 is that the temperature of the carbon nanotube layer preparation process was changed, that is, the thickness of the carbon nanotube layer was 500 μm under high temperature and high pressure of 900℃.

[0114] Example 5:

[0115] The difference from Example 1 is that the preparation process of carbon-coated camphor particles was changed, the mass fraction of sucrose water was controlled to be 3 parts, the temperature in the tube furnace was 200°C, and the carbon shell thickness in the resulting carbon-coated camphor particles was 15 nm.

[0116] Comparative Example 1:

[0117] The mass fractions of each substance are as follows: graphite (raw material is secondary particles): 96.8 parts, PAA: 0.6 parts, SBR: 1.2 parts, CMC: 0.6 parts, SP: 0.4 parts, CNT: 0.4 parts, and deionized water: 185 parts. The above amounts of graphite powder, SP, and CMC were added to a mixing tank and dry-mixed for 30 minutes at a stirring speed of 15 rpm and a dispersion speed of 500 rpm. Then, 80 parts of deionized water were added and kneaded for 60 minutes at a stirring speed of 20 rpm and a dispersion speed of 300 rpm. Next, the remaining deionized water (105 parts) was added and dispersed at high speed at a stirring speed of 22 rpm and a dispersion speed of 1000 rpm. Then, CNT and PAA were added and dispersed for 30 minutes at a stirring speed of 22 rpm and a dispersion speed of 600 rpm. Finally, SBR was added and mixing continued for 30 minutes at a stirring speed of 22 rpm and a dispersion speed of 500 rpm, resulting in the first coating slurry.

[0118] The first coating slurry was applied to the copper foil, with a coating surface density of 210 g / m². 2 The coated electrode sheets are then rolled to achieve a compaction density of 1.5 g / cm³. 3 between.

[0119] Comparative Example 2:

[0120] The difference from Example 1 is that the preparation of the carbon nanotube layer in step (2) is not included.

[0121] Comparative Example 3:

[0122] The difference from Example 1 is that the preparation of carbon-coated camphor particles in step (3) is not included. In step (4), the mass fractions of each substance in the preparation of the second coating slurry are as follows: graphite (raw material is primary particles): 97 parts, PAA: 0.6 parts, SBR: 0.8 parts, CMC: 0.6 parts, SP: 0.4 parts, second camphor particles: 0.6 parts, deionized water: 185 parts. Among them, the second camphor particles are still the second camphor particles provided in step (3), but the outer shell is not coated with a carbon shell.

[0123] Electrode wettability test, electrode conductivity test, and electrochemical performance test were performed on the above embodiments and comparative examples in sequence. The negative electrode provided by the above embodiments and comparative examples were used to prepare secondary batteries and the results were summarized and recorded in Table 1.

[0124] Electrode wettability test: The wettability of an electrode is reflected in its absorption capacity and the amount absorbed per unit time. Typically, the wettability test compares the absorption rate of different electrode sheets of the same weight to the same amount of electrolyte; the electrode that absorbs the electrolyte first has a stronger absorption capacity. It also compares the absorption and storage capacity of different electrode sheets of the same weight immersed in electrolyte; the heavier electrode has a stronger absorption capacity. The negative electrode sheets prepared in the examples and comparative examples were used to test the electrolyte absorption rate and absorption capacity, respectively.

[0125] Electrode conductivity testing: Conductivity testing mainly involves testing the film resistance of the electrode sheets used in batteries. The test method involves measuring the resistance value of the film per unit area under unit pressure. The film resistance of the negative electrode sheets prepared in the example and comparative examples are tested.

[0126] Electrochemical performance testing: The test temperature was 25±2℃. The battery was charged at a constant power of 0.5C to 3.65±0.01V; allowed to rest for 10 minutes, then discharged at 0.5P (discharge rate), with a cutoff voltage of 2.5V. This capacity was recorded as the initial capacity for the rate test. The battery was then charged at a constant current of 1C to 3.65±0.01V; allowed to rest for 10 minutes; then discharged at 1P, with a cutoff voltage of 2.5V. This capacity was recorded as the 1P rate capacity. Here, C-rate (C for short) is a value relative to the battery's rated capacity. For example, if a battery's rated capacity is 200Ah, then 1C is equivalent to a charging or discharging rate of 200A. According to this definition, 0.5C means the battery can be fully charged in 2 hours, while 1C means the battery can be fully charged in 1 hour. Similarly, 0.5P means the battery can be fully discharged in 2 hours, while 1P means the battery can be fully discharged in 1 hour.

[0127] Table 1

[0128]

[0129]

[0130] As shown in Table 1, compared with Comparative Example 1, Examples 1 to 5 include adding first camphor particles in the preparation process of the first active layer, forming a carbon nanotube layer after forming the first active layer, and adding second camphor particles in the preparation process of the second active layer. The outer layer of the second camphor particles is also coated with a carbon shell, which can improve the rate at which the negative electrode absorbs the electrolyte and reduce the resistance of the negative electrode to obtain better rate performance.

[0131] The experimental data from Example 1 and Comparative Example 2 show that the carbon nanotube layer can reduce the resistance of the negative electrode, but at the same time it will affect the absorption of electrolyte. Therefore, based on the data from Example 4, it can be seen that controlling the thickness of the carbon nanotube layer can ensure that the negative electrode can be reduced while having good absorption of electrolyte.

[0132] As can be seen from the experimental data of Example 1 and Comparative Example 3, the first camphor particles are formed in the first active layer, that is, the first pores are formed, but the second pores are not formed in the second active layer, the absorption rate of the electrolyte is low and the resistance is high.

[0133] Those skilled in the art will understand that the above embodiments are specific examples of implementing this application, and in practical applications, various changes in form and detail can be made without departing from the spirit and scope of this application. Any person skilled in the art can make various alterations and modifications without departing from the spirit and scope of this application; therefore, the scope of protection of this application should be determined by the scope defined in the claims.

Claims

1. A secondary battery, characterized in that, include: A battery casing having a cavity inside, and an electrolyte being contained within the cavity; A bare battery cell, wherein the bare battery cell is located within the cavity and immersed in the electrolyte; The bare battery cell includes a positive electrode, a separator, and a negative electrode stacked together. The negative electrode includes a negative current collector, a first active layer, and a second active layer. The first active layer is located on the surface of the current collector, and the second active layer is located on the surface of the first active layer. The second active layer has a second pore enclosed by a carbon shell, and the second porosity of the second active layer is greater than the first porosity of the first active layer. The electrolyte is located within the second pore.

2. The secondary battery according to claim 1, characterized in that, The second pore is formed by the sublimation of the second camphor particles; the second particle size of the second camphor particles is 5μm to 10μm.

3. The secondary battery according to claim 2, characterized in that, The first active layer has a first pore, and the electrolyte is located in the first pore. The first pore is formed by the sublimation of the first camphor particles, and the first particle size of the first camphor particles is 15μm to 20μm.

4. The secondary battery according to claim 3, characterized in that, The second particle size of the second camphor particle is smaller than the first particle size of the first camphor particle.

5. The secondary battery according to claim 1, characterized in that, The negative electrode further includes a carbon nanotube layer, which is located between the first active layer and the second active layer.

6. The secondary battery according to claim 1, characterized in that, The thickness of the carbon nanotube layer is 200 μm to 500 μm.

7. A method for preparing a secondary battery, characterized in that, include: A negative electrode sheet is formed, the negative electrode sheet comprising: a negative electrode current collector, a first active layer and a second active layer stacked sequentially; the preparation step of forming the second active layer includes: preparing carbon-coated camphor particles; Prepare a second coating slurry, the second coating slurry comprising the carbon-coated camphor particles; The second coating slurry is applied to the negative electrode current collector having the first active layer and then dried to form the second active layer; wherein, during the drying process, the camphor particles in the carbon-coated camphor particles sublimate to form the second pores. A positive electrode and a separator are provided. The negative electrode, separator and positive electrode are stacked in sequence. A bare cell is obtained by winding or stacking. The bare cell is placed into a battery case. Electrolyte is injected into the battery case and then packaged to obtain a secondary battery.

8. The method for preparing a secondary battery according to claim 1, characterized in that, The second coating slurry further includes: a second negative electrode material, a second conductive agent, a second binder, and a second dispersion solution; the mass ratio of the carbon-coated camphor particles, the second negative electrode material, the second conductive agent, the second binder, and the second dispersion solution is (0.4-0.6):(96-97.2):(0.4-0.6):(2.0-2.8):(160-200).

9. The method for preparing a secondary battery according to claim 8, characterized in that, The second adhesive comprises styrene-butadiene rubber, carboxymethyl cellulose, and polyacrylic acid, wherein the mass ratio of styrene-butadiene rubber, carboxymethyl cellulose, and polyacrylic acid is (0.8-1.2):(0.6-0.8):(0.6-0.8).

10. The method for preparing a secondary battery according to claim 9, characterized in that, In the process of obtaining the second coating slurry, the carboxymethyl cellulose, the polyacrylic acid, and the styrene-butadiene rubber are added sequentially, while the stirring speed is controlled to first increase and then decrease.

11. The method for preparing a secondary battery according to claim 1, characterized in that, The preparation steps of the carbon-coated camphor particles include: dispersing second camphor particles in a pre-carbonization solution containing carbonizing material, drying to obtain a camphor precursor, the surface of which is coated with the carbonizing material; heat-treating the camphor precursor to convert it into the carbon-coated camphor particles; the pre-carbonization solution includes a sucrose aqueous solution, the sucrose aqueous solution accounting for 3 to 7 parts by mass of the pre-carbonization solution; and the second camphor particles accounting for 55 wt% to 70 wt% by mass of the sucrose aqueous solution.

12. The method for preparing a secondary battery according to claim 11, characterized in that, The heat treatment process includes: placing the camphor precursor in a heat treatment device, introducing an inert gas, heating to 160℃~200℃, carbonizing for 5min~15min, and cooling to obtain the carbon-coated camphor particles; the thickness of the carbon shell in the carbon-coated camphor particles is 15nm~20nm.

13. The method for preparing a secondary battery according to claim 11, characterized in that, The preparation steps for forming the first active layer include: The first camphor particles, the first negative electrode material, the first conductive agent, and the first binder are stirred evenly with the first dispersion solution. The first coating slurry is obtained; The first coating slurry is applied to the negative electrode current collector at a density of 100 g / m³. 2 ~110g / m 2 After drying, the first active layer is obtained, wherein the first camphor particles sublimate after drying, and the positions occupied by the first camphor particles are transformed into first pores, and the second coating slurry flows into at least part of the first pores.

14. The method for preparing a secondary battery according to claim 13, characterized in that, After forming the first active layer, the process further includes: providing a carbon source gas and a carrier gas, and forming a carbon nanotube layer on the surface of the first active layer using a plasma vapor deposition process at a temperature of 700℃ to 900℃; the thickness of the carbon nanotube layer is 200μm to 500μm.

15. The method for preparing a secondary battery according to claim 13, characterized in that, The second particle size of the second camphor particle is smaller than the first particle size of the first camphor particle; the first particle size is 15μm to 20μm; the second particle size is 5μm to 10μm.

16. The method for preparing a secondary battery according to claim 13, characterized in that, The mass ratio of the first camphor particles, the first negative electrode material, the first conductive agent, the first binder, and the first dispersion solution is (0.2-0.4):(96-97.2):(0.8-1.2):(2.0-2.8):(160-200).

17. The method for preparing a secondary battery according to claim 16, characterized in that, The first conductive agent comprises carbon nanotubes and conductive carbon black, and the mass ratio of the carbon nanotubes to the conductive carbon black is (0.4-0.6):(0.4-0.6).

18. An energy storage battery pack, characterized in that, include: The secondary battery prepared by the method of any one of claims 7 to 17, or the secondary battery as described in claims 1 to 6.

19. An electrical appliance, characterized in that, include: The secondary battery prepared by the method of any one of claims 7 to 17, the secondary battery as described in claims 1 to 6, or the energy storage battery pack as described in claim 18.

Citation Information

Cited By

  • Negative plate and preparation method thereof

    CN121641834A